A kind of polypropylene material and its preparation method and application

By using a mixture of alumina powder with a combination of large and small particle sizes and a silane coupling agent in the polypropylene material, the problem of the existing high-gloss polypropylene materials being easily scratched is solved, and high gloss and good scratch resistance is achieved.

CN117757179BActive Publication Date: 2025-03-18CHENGDU KINGFA SCI & TECH ADVANCED MATERIALS CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311651838.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-05
Publication Date
2025-03-18
Estimated Expiration
2043-12-05

AI Technical Summary

Technical Problem

The existing high-gloss polypropylene materials are prone to deterioration in appearance due to hard objects during use, and their scratch resistance is insufficient.

Method used

A mixture of alumina powders of a combination of large and small particle sizes is used to fill polypropylene, and a silane coupling agent is used as a dispersant to enhance the interaction between alumina and matrix, and improve the gloss and scratch properties of the material.

Benefits of technology

The high gloss and good scratch resistance of polypropylene material are achieved, and the scratches are shallow, so that the material is easily scratched by hard objects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117757179B_ABST
    Figure CN117757179B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of polymer materials, and discloses a polypropylene material, a preparation method and an application thereof. The polypropylene material of the present invention comprises the following components by weight: 69-90 parts of polypropylene, 5-15 parts of alumina powder mixture, 0.2-1 parts of silane coupling agent, 0-1 parts of primary antioxidant, 0-1 parts of secondary antioxidant, and 0-1 parts of light stabilizer. The present invention uses a mixture of alumina powder with large and small particle sizes to fill polypropylene, which improves the material's ability to resist deformation during scratching, makes scratches shallow, avoids the material from being easily scratched by hard objects, and has little effect on gloss. It is suitable for the fields of automotive parts and home appliance housings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to the field of polypropylene material modification, and specifically to a polypropylene material with high gloss and scratch resistance, and a preparation method and application thereof. Background Art

[0002] Polypropylene, referred to as PP, is a polymer formed by polyaddition of propylene. Since polypropylene has the advantages of low density, good strength, rigidity and heat resistance, and low cost, it is widely used in the automotive industry, household electronic appliances, packaging, building materials and other fields. In parts such as automotive decorative parts or household appliance housings, the products are often required to have a high-gloss appearance, so high-gloss polypropylene materials are required. Chinese invention patent document CN101100539 A uses homopolymer polypropylene as the matrix, fills with nano-calcium carbonate, and obtains a high-gloss polypropylene material by modifying a nucleating agent and a cross-linking agent. Chinese invention patent document CN104086939 A uses copolymer polypropylene as the matrix, uses mineral filling, and ethylene-octene toughening to obtain high-gloss polypropylene, but the polypropylene material of the above scheme has a low gloss. The hardness of the polypropylene material itself is low, and the surface is easily scratched, resulting in the high-gloss polypropylene material being easily scratched by hard objects during use and the appearance deteriorating. Therefore, it is urgent to develop a polypropylene material that can take into account both high gloss and scratch resistance. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a polypropylene material having both high gloss and scratch resistance and a preparation method and application thereof.

[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0005] In a first aspect, the present invention provides a polypropylene material, comprising the following components by weight: 69-90 parts of polypropylene, 5-15 parts of alumina powder mixture, 0.2-1 parts of silane coupling agent, 0-1 parts of primary antioxidant, 0-1 parts of secondary antioxidant, and 0-1 parts of light stabilizer;

[0006] The alumina powder mixture comprises alumina powder A with an average particle size of 200nm to 500nm and alumina powder B with an average particle size of 2.6μm to 4.3μm; the mass ratio of the alumina powder A to the alumina powder B is 6 to 8:2 to 4;

[0007] In the polypropylene material, the content of polypropylene resin is not less than 70%.

[0008] The polypropylene material of the present invention uses a mixture of alumina powders of large and small particle sizes to fill polypropylene. The large particle size promotes the dispersion of the small particle size, and the small particle size is dispersed and bridged around the large particle size, which prevents the large particle size alumina from being plowed out by a needle, so that the polypropylene material has high gloss and good scratch resistance, which can significantly improve the dispersibility of alumina, improve the surface gloss of the material, and improve the scratch resistance. The hardness of alumina (i.e., aluminum oxide) is relatively high, which improves the material's ability to resist deformation during the scratching process, making the scratches shallower and preventing the material from being easily scratched by hard objects. Alumina powder with large particle size avoids alumina agglomeration and promotes dispersion, and alumina powder with small particle size makes the surface distribution uniform, giving full play to the effect of improving the surface hardness of the material, and the particle size of the alumina powder mixture is relatively small, which has little effect on the gloss.

[0009] Preferably, the alumina may be spherical alumina.

[0010] Preferably, the mass ratio of the alumina powder A to the alumina powder B is 2 to 3:1; further, the mass ratio of the alumina powder A to the alumina powder B is 2 to 2.5:1.

[0011] Preferably, in the polypropylene material, the weight proportion of the alumina powder mixture can be selected to be any of 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 parts or a range of both parts.

[0012] As a preferred embodiment of the polypropylene material of the present invention, the polypropylene is homopolymer polypropylene and / or random copolymer polypropylene. The melt flow rate of the polypropylene is 1 g / 10 min to 100 g / 10 min (tested according to ISO 1133-1:2022, temperature 230°C, load 2.16 kg).

[0013] In the polypropylene material, the content of polypropylene is not less than 70%.

[0014] Preferably, the weight proportion of the polypropylene can be selected from any of 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, and 90 parts, or a range of both parts.

[0015] As a preferred embodiment of the polypropylene material of the present invention, the silane coupling agent is at least one of vinyl silane, amino silane and methacryloxy silane; preferably, the silane coupling agent is amino silane, such as γ-aminopropyltriethoxy silane.

[0016] The polypropylene material of the present invention adopts a silane coupling agent as a dispersant, and the coupling agent enhances the interaction between alumina and the matrix, so that the alumina powder is well dispersed in the matrix, which not only improves the glossiness, but also strengthens the effect of the filler and the matrix, so that the deformation resistance of the matrix is ​​improved and the degree of scratch damage is reduced.

[0017] As a preferred embodiment of the polypropylene material of the present invention, the primary antioxidant is a hindered phenol compound; preferably, the primary antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1010).

[0018] As a preferred embodiment of the polypropylene material described in the present invention, the auxiliary antioxidant is a phosphite compound; preferably, the auxiliary antioxidant is tris(2,4-di-tert-butylphenyl)phosphite (antioxidant 168).

[0019] As a preferred embodiment of the polypropylene material described in the present invention, the light stabilizer is a hindered amine compound; preferably, the light stabilizer is C12-21 and C18-unsaturated fatty acid-2,2,6,6-tetramethyl-4-piperidinyl ester (light stabilizer UV-3808PP5).

[0020] In a second aspect, the present invention provides a method for preparing the polypropylene material, comprising the following steps:

[0021] Take the components according to weight, mix them evenly, and melt-extrude them into granules to obtain the product;

[0022] As a preferred embodiment of the preparation method described in the present invention, the conditions for melt extrusion are: zone one temperature 80°C ~ 120°C, zone two temperature 180°C ~ 200°C, zone three temperature 180°C ~ 220°C, zone four temperature 180°C ~ 220°C, zone five temperature 180°C ~ 220°C, zone six temperature 180°C ~ 220°C, zone seven temperature 180°C ~ 220°C, zone eight temperature 180°C ~ 220°C, zone nine temperature 180°C ~ 220°C; main engine speed 400r / min ~ 500r / min; the aspect ratio of the twin-screw extruder is 35 ~ 45:1.

[0023] In a third aspect, the present invention applies the polypropylene material to automobile parts and household appliance casings.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The polypropylene material of the present invention uses a mixture of alumina powders of large and small particle sizes to fill polypropylene. The hardness of alumina is relatively high, which improves the material's ability to resist deformation during scratching, makes scratches shallow, and prevents the material from being easily scratched by hard objects. Alumina powders with large particle sizes prevent alumina from agglomerating and promote dispersion. Alumina powders with small particle sizes make the surface distribution uniform, giving full play to the effect of improving the surface hardness of the material. In addition, the particle size of the alumina powder mixture is relatively small, which has little effect on gloss. Silane coupling agent is used as a dispersant. The coupling agent improves the interaction between alumina and the matrix, so that the alumina powder is well dispersed in the matrix, which not only improves the gloss, but also strengthens the role of the filler and the matrix, so that the matrix's ability to resist deformation is improved and the degree of damage caused by scratching is reduced. It is suitable for the fields of automotive parts and home appliance housings. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The secondary optical measurement of the polypropylene material after scratching of Example 1;

[0027] Figure 2 The secondary optical measurement of the polypropylene material after scratching of Example 2;

[0028] Figure 3 The secondary optical measurement of the polypropylene material of Comparative Example 1 after scratching;

[0029] Figures 1 to 3 The magnification is 65 times. DETAILED DESCRIPTION

[0030] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0031] In the following examples and comparative examples, unless otherwise specified, the primary antioxidant, the secondary antioxidant and the light stabilizer are all commercially available, and the same primary antioxidant, the secondary antioxidant and the light stabilizer are used in the parallel experiments.

[0032] In the following embodiments, the performance detection method is:

[0033] The scratch resistance is tested according to the five-finger scratch method FORD FLTM BN 108-13, with a load of 10N. The width of the scratch is used to evaluate the degree of damage to the sample. The smaller the width, the lower the degree of material damage and the better the scratch resistance.

[0034] Glossiness: The surface of the injection molded sample is tested with a gloss meter to test the glossiness at 60°.

[0035] The raw materials used in the following examples and comparative examples are described as follows, but are not limited to these materials:

[0036] Homopolymer polypropylene, brand N-Z30S, purchased from Maoming Petrochemical;

[0037] Random copolymer polypropylene, brand PP RP346R, purchased from CNOOC Shell;

[0038] Alumina powder 0.2 μm, aluminum oxide, average particle size 200 nm, purchased from Hebei Zhuyan Alloy Materials Co., Ltd.;

[0039] Alumina powder 0.5 μm, aluminum oxide, average particle size 500 nm, purchased from Hebei Zhuyan Alloy Materials Co., Ltd.;

[0040] Alumina powder 1 μm, aluminum oxide, average particle size 1000 nm, purchased from Hebei Zhuyan Alloy Materials Co., Ltd.;

[0041] Alumina powder 2.6 μm, aluminum oxide, average particle size 2600 nm, purchased from Jingliangda Chemical;

[0042] Alumina powder 4.3 μm, aluminum oxide, average particle size 4300 nm, purchased from Lanke Environmental Protection Water Purification Material Factory;

[0043] Alumina powder 6.5 μm, aluminum oxide, average particle size 6500 nm, purchased from Jingliangda Chemical;

[0044] The above-mentioned alumina powder is spherical. The average particle size of the above-mentioned alumina powder is measured with reference to GB / T 19077-2016 standard. The above-mentioned micron-grade alumina powder is sieved and graded before use, and the particle size is tested to achieve the corresponding particle size.

[0045] Precipitated barium sulfate, average particle size 1.5 μm, brand AB-3000N1, purchased from Guangzhou Huangpu Tiantai Chemical Co., Ltd.;

[0046] Talc, 3000 mesh, brand TYT-777A, purchased from Haicheng Tianyuan Chemical Co., Ltd.

[0047] Vinylsilane, vinyltri(2-methoxyethoxy)silane, brand SG-SI 172, purchased from Nanjing Shuguang Chemical Group Co., Ltd.;

[0048] Aminosilane, γ-aminopropyltriethoxysilane, brand JH-A110, purchased from Jingzhou Jianghan Fine Chemical Co., Ltd.;

[0049] Amide lubricant, brand EBS B50, purchased from Guangzhou Runfeng Chemical Co., Ltd.

[0050] Primary antioxidant, antioxidant 1010, commercially available;

[0051] Secondary antioxidant, antioxidant 168, commercially available;

[0052] Light stabilizers, UV-3808PP5, effective content of light stabilizer is 50%, carrier resin is PP, the amount of light stabilizer added in Table 1 has been converted into pure light stabilizer; commercially available.

[0053] The components of the polypropylene materials of Examples 1 to 8 and Comparative Examples 1 to 9 are shown in Table 1.

[0054] The preparation methods of the polypropylene materials of Examples 1 to 8 and Comparative Examples 1 to 9 are as follows:

[0055] Homopolymer polypropylene or random copolymer polypropylene, alumina powder, vinyl silane or γ-aminopropyl triethoxysilane, primary antioxidant, secondary antioxidant and light stabilizer are put into a high-speed mixer and stirred thoroughly to obtain a premix, and the premix is ​​placed at the main feeding port of a twin-screw extruder for melt extrusion, granulation and drying to obtain the product.

[0056] Among them, the melt extrusion conditions of the twin-screw extruder are: zone 1 temperature 90°C, zone 2 temperature 180°C, zone 3 temperature 200°C, zone 4 temperature 200°C, zone 5 temperature 200°C, zone 6 temperature 200°C, zone 7 temperature 200°C, zone 8 temperature 200°C, zone 9 temperature 200°C, main engine speed 450r / min; the aspect ratio of the twin-screw extruder is 40:1.

[0057] Table 1: Example polypropylene material components (weight parts) and test results

[0058]

[0059]

[0060] Table 2: Comparative Example Polypropylene Material Components (Parts by Weight) and Their Test Results

[0061]

[0062] The polypropylene material of the embodiment of the present invention has high gloss and is scratch-resistant. The glossiness of the material is 85 to 89 (preferably 87 to 89), and the scratch width is 0.351 mm to 0.376 mm (preferably 0.351 mm to 0.359 mm).

[0063] The polypropylene materials of Examples 1 and 2 have high gloss and excellent scratch resistance. Figure 1 and Figure 2 As shown in the figure, after the five-finger scratch test, the scratch is very shallow and small in width, and the surface is not scratched, but there is a slight scratch mark. The material has excellent scratch resistance.

[0064] Compared with Example 1, the polypropylene material of Comparative Example 1 uses precipitated barium sulfate. Although the glossiness of the polypropylene material is high, it is easy to be scratched and deformed due to the low hardness of the material surface. Figure 3 As shown in the figure, after the five-finger scratch test, the scratch is relatively wide and the surface scratch is obvious (many undulations can be seen on the surface). The polypropylene material of Comparative Example 2 is filled with talcum powder. Since the talcum powder itself has a low glossiness and affects the surface roughness of the polypropylene surface, the glossiness of the polypropylene material is low, and the talcum powder itself has a low hardness, which makes the scratch resistance of the polypropylene material poor.

[0065] Compared with Example 2, the polypropylene material of Comparative Example 3 uses amide lubricant, which cannot effectively disperse the aluminum oxide powder, resulting in powder agglomeration, low gloss, and easy scratching, resulting in poor scratch performance.

[0066] In the polypropylene material of comparative example 4, the content of 0.2 micron aluminum oxide powder is relatively high, which is not easy to disperse and is easy to agglomerate, resulting in some pitting on the surface that affects the glossiness. The agglomerated aluminum powder is easily scraped off during scratching, causing serious damage to the surface of the material, resulting in poor scratch performance of the polypropylene material.

[0067] Compared with Example 5, the polypropylene material of Comparative Example 5 has a higher content of 4.3 micron aluminum oxide powder, and the interface between the large-particle aluminum powder and the polypropylene matrix is ​​obvious and easily damaged. When scratching, the needle easily scrapes the matrix and the aluminum powder apart, resulting in obvious scratches on the polypropylene material. At the same time, the interface obviously causes light scattering and reduces the surface gloss. In the polypropylene material of Comparative Example 6, the total weight of aluminum oxide powder remains unchanged, but the proportion of large-particle size is too large, resulting in poor gloss and scratch resistance of the polypropylene material.

[0068] Compared with Example 2, in the polypropylene material of Comparative Example 7, the total weight of aluminum oxide powder remains unchanged, but the proportion of small particle size is too large, resulting in poor scratch resistance of the polypropylene material.

[0069] In the polypropylene material of Comparative Example 8, nano-alumina is combined with micron-alumina having too small a particle size, resulting in poor scratch resistance of the polypropylene material; in the polypropylene material of Comparative Example 9, nano-alumina is combined with micron-alumina having too large a particle size, resulting in low gloss and poor scratch resistance of the polypropylene material.

[0070] The polypropylene material of the present invention adopts a reasonable combination of large and small particle size aluminum powders. The large particle size promotes the dispersion of the small particle size, and the small particle size is dispersed around the large particle size to bridge the large particle size, thereby preventing the large particle size aluminum oxide from being plowed out by the needle, so that the polypropylene material has high gloss and good scratch resistance.

[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A polypropylene material, characterized in that: By weight, it includes the following components: Polypropylene 69-90 parts, alumina powder mixture 5-15 parts, silane coupling agent 0.2-1 parts, primary antioxidant 0-1 parts, auxiliary antioxidant 0-1 parts, light stabilizer 0-1 parts; The alumina powder mixture comprises alumina powder A with an average particle size of 200nm-500nm and alumina powder B with an average particle size of 2.6μm-4.3μm; the mass ratio of the alumina powder A to the alumina powder B is 6-8:2-4.

2. The polypropylene material according to claim 1, characterized in that: The polypropylene is homopolymer polypropylene and / or random copolymer polypropylene.

3. The polypropylene material according to claim 1, characterized in that: The silane coupling agent is at least one of vinyl silane, amino silane and methacryloxy silane.

4. The polypropylene material according to claim 1, characterized in that: The primary antioxidant is a hindered phenol compound.

5. The polypropylene material according to claim 1, characterized in that: The auxiliary antioxidant is a phosphite compound.

6. The polypropylene material according to claim 1, characterized in that: The light stabilizer is a hindered amine compound.

7. The method for preparing the polypropylene material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The components are taken in parts by weight, mixed evenly, melt-extruded and granulated to obtain the product.

8. Use of the polypropylene material according to any one of claims 1 to 6 in automobile parts and housings of household appliances.

Citation Information

Patent Citations

  • High glaze polypropylene material and preparation method thereof

    CN101100539A

  • High-modulus high-toughness high-glossiness polypropylene and preparation method thereof

    CN104086939A

  • Abrasion-resistant anti-permeability epoxy protective coating and preparation method thereof

    CN105038504A

  • Aluminum nitride / needle-shaped aluminum oxide filled cold-touch polypropylene composite material and preparation method thereof

    CN116874929A